Relación existente entre las actitudes y prácticas ambientales predominantes de los estudiantes del I nivel de la escuela de ingeniería en gestión ambiental. UNAP.2022 - Rios Flores de Reategui, Paola del Carmen (2022)
The study called: "Existing relationship between the prevailing environmental attitudes and practices of the students of the I level of the school of engineering in environmental management. UNAP. 2022. The objectives were: to establish the existing relationships between the environmental attitudes and practices of the students of the first level of the Professional School of Environmental Management - Faculty of Agronomy - UNAP. The research work is descriptive-cross-sectional. Having a simple and convenience probabilistic sample of 25 people from the total number of students enrolled in the semester. From the results Applying the Likert test, it is concluded that there is a good relationship between attitudes and ecological behaviors in the students of the I Level of the Professional School of Environmental Management.The results achieved were developed through descriptive statistics.On the cleaning of the public spaces exposed to urban waste, they always collect their waste in a bin s (44%), avoid throwing their waste on the ground (68%), do not litter the streets (40%), and keep them clean (52%), keep their waste or paper in their pockets (72%). As for saving water, when they carry out personal toilets they never leave the stream open (64%), with what they think they are always taking care of the water (72%). Regarding saving electricity, they never leave the lights on (48%), turn off the lights when not in use 68%, avoid wasting energy (52%) and never leave the television on (48%). In the collaboration with environmental institutions, they collaborate with it (36%) almost always, they always talk with friends or other people about the environment (40%), they always avoid wasting natural resources (40%), as well as the purchase of plastic, almost never (36%). There is participation in volunteering (32%), I cooperate with the preservation of my city (40%).